The Study of the Variation of the Hydrological Regime in a Representative Hydrographic Basin During a Hydrological Cycle - Erika Beata Maria BEILICCI; Robert Florin BEILICCI (Aerul şi Apa: Componente ale Mediului, 2024)
The study of the variation of the hydrological regime in hydrographic basins is a necessity in the context of climate change. Based on the forecast of flow and level variations, water resources management plans are drawn up. The paper deals with the subject of simulating the phenomenon of rainfall - runoff with the help of the advanced hydroinformatics tool MIKE by DHI. The data used represent the precipitation and flows recorded in the Turnu Ruieni section, on the Sebes river, between the years 1988-1997, 2005, respectively the year 2021. A comparison is made of the maximum discharge values obtained from the simulation in the years 1988-1997, 2005 and 2021 (the difference of 33 years, approximately the duration of a hydrological cycle); a comparison is made between the discharges on the Sebeș River, in the years 1988-1997, 2005 and 2021, respectively between the amounts of recorded precipitation. The MIKE11byDHI program is used, the Rainfall – Runoff (RR) module, based on the UHM (Unit Hydrograph Model), the CN “Curve Number” method, the SCS (Soil Conservation Service) method.